2001
DOI: 10.1063/1.1352700
|View full text |Cite
|
Sign up to set email alerts
|

Uniform deposition of ultrathin polymer films on the surfaces of Al2O3 nanoparticles by a plasma treatment

Abstract: Surface modification of nanoparticles will present great challenges due to their extremely small dimensions, high surface areas, and high surface energies. In this research, we demonstrate the uniform deposition of ultrathin polymer films of 2 nm on the surfaces of alumina nanoparticles. The deposited film can also be tailored to multilayers. Time-of-flight secondary ion mass spectroscopy was used to confirm the pyrrole thin film on the nanoparticle surfaces. Using such a nanocoating, it is possible to alter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
65
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 12 publications
0
65
0
Order By: Relevance
“…Plasma nanocoatings/modifications have been used to reduce agglomerations by modifying the surface of nanomaterials [9]. Plasma nanocoating of individual nanoparticles in particular proves effective in breaking up nanoparticle agglomeration [10][11][12][13][14][15][16][17]. Plasma nanocoatings generally contain functional groups which electrostatically prevent agglomeration and can also enhance interactions with the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma nanocoatings/modifications have been used to reduce agglomerations by modifying the surface of nanomaterials [9]. Plasma nanocoating of individual nanoparticles in particular proves effective in breaking up nanoparticle agglomeration [10][11][12][13][14][15][16][17]. Plasma nanocoatings generally contain functional groups which electrostatically prevent agglomeration and can also enhance interactions with the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…An important factor, that is directly related to the size of nanotubes, is that the surface energy of these particles can be so high, i.e., several hundreds of mJ/mÂČ, that the organic monomer is very strongly and uniformly adsorbed on them. It was observed, for instance, in our preliminary work with nanosize Al 2 O 3 and ZnO particles [6][7][8][9]. The film structure is then mainly determined by ion and radiation impact of adsorbed monomer and much less by the radicals formed in the plasma.…”
mentioning
confidence: 83%
“…In our previous works we developed new nano structures by a unique plasma treatment for the synthesis of polymer composites [6][7][8][9][10]. The unique properties required in these composites have been shown to be best achieved by our plasma method.…”
Section: Introductionmentioning
confidence: 99%
“…Inagaki et al [5] reported surface modification of polyethylene powders using a fluidised bed. Later, van Ooij et al [6][7][8] reported surface modification of various powder substrates using different reactors, which included a vertical tubular reactor, a tumbler reactor and a fluidised bed reactor.…”
Section: Introductionmentioning
confidence: 99%